Estimation of radon and natural radioactive emissions from two of the most widely used construction materials in Egypt - Abd-Elghany, Amr A.; Diab, Hassan M.; Yousef, Ahmed M. M.; Saleh, Hosam M. (Frontiers in Built Environment, 2023)
As the risk of lung cancer increases with increasing radon exposure, the preferred measure of this risk is the long-term average radon level. The assessment of the radiation risk in workplaces in Egypt is constrained by the lack of experimental data about the measurements of natural radioactivity emitted from some common building materials and radon concentration within the buildings. The natural radioactive Ra-226, Th-232 series, and K-40 were computed in (Bq/kg) by a pure hyperactive germanium detector based on gamma spectroscopy to determine the potential health risk from exposure to gamma radiation induced by commonly used construction materials in Egypt such as ceramics and granite materials. The spatial variations of radon concentrations within two buildings, in over 50 rooms, made from two different types of building materials were surveyed using nuclear detectors (CR-39) to assess radon concentration for two successive 6 months. To analyze the relationship through radon concentration and floor levels for the use of ceramic tile improved construction materials, tier average ratios respecting the ground floor as a reference-grade consideration were also computed. All the findings of this research were analyzed and contrasted with the traditional ceramic construction material and it was clear that the "ceramics tile construction building" is a hygienic workplace which may be attributed to the use of improved construction materials and radiation shielding.